The conscientious gardener : cultivating a garden ethic - Reichard, Sarah H. (University of California Press, 2011)
"In his influential A Sand County Almanac, published at the beginning of the environmental movement in 1949, Aldo Leopold proposed a new ecological ethic to guide our stewardship of the planet. In this inspiring book, Sarah Hayden Reichard tells how we can bring Leopold's far-reaching vision to our gardens to make them more sustainable, lively, and healthy places. Today, gardening practices too often damage the environment: we deplete resources in our own soil while mining for soil amendments in far away places, or use water and pesticides in ways that can pollute lakes and rivers. Drawing from cutting edge research on urban horticulture, Reichard explores the many benefits of sustainable gardening and gives straightforward, practical advice on topics such as pest control, water conservation, living with native animals, mulching, and invasive species. The book includes a scorecard that allows readers to quickly evaluate the sustainability of their current practices, as well as an extensive list of garden plants that are invasive, what they do, and where they should be avoided."--